Social support in a large general population sample over the course of six years - Andreas Hinz; Peter Esser; Diana Richter; Antje Schönfelder; Heide Glaesmer; Antje Lehmann-Laue; Svenja Heyne; Katja Leuteritz; Annekathrin Sender; Franziska Springer; Heide Götze; Anja Mehnert-Theuerkauf (Scientific Reports, 2025)
Abstract Social support is an important resource that is assumed to buffer the effect of stressful events on health. The aims of this study were to test psychometric properties of the ENRICHD Social Support Instrument (ESSI), to investigate the impact of several sociodemographic and behavioral variables on social support, and to analyze changes in social support over a 6-year period. A sample of 9,681 people from the general population was examined at baseline, 4,987 of whom were surveyed at a follow-up examination six years later using the ESSI and several other questionnaires. The psychometric properties of the ESSI were good (Cronbach’s α = 0.91) and measurement invariance across gender and age could be established. High socioeconomic status, sharing a household with others, and employment resulted in high levels of social support. Tobacco smokers and alcohol drinkers reported having less social support than nonsmokers and non-drinkers. During the 6-year period, the mean level of social support remained nearly unchanged (d = 0.01). The data provide a framework for the interpretation and comparison of social support with other clinical and nonclinical populations. Public health initiatives should aim to prevent social isolation to improve public health.